Rational Emotive Behavior Therapy (REBT) to Reduce Self-Harm Behavior in Adolescents in Terms of Big Five Personality Traits - Muhamad Gandhi; Noviekayati, IGAA; Santi, Dyan Evita (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine Rational Emotive Behavior Therapy in reducing Self-Harm behavior in adolescents and to examine differences in Self-Harm behavior in adolescents regarding Big Five Personality Traits. This study's research sample was 200 students in X school aged 15-20. Six subjects who met the criteria were obtained after screening using the Self-Harm scale measurement and personality dimension assessment using the Big Five Personality Traits scale. The research was conducted using an experimental method. This research uses a Pre-experiment with one group pretest and posttest design method. This research instrument is the Self-Harm scale and Big Five Personality Traits. Data analysis in this study used the Wilcoxson Signed Rank Test statistical test and the Kruskall Wallis test. The results of the Wilcoxson Signed Rank Test showed an Asymp. Sig (2-tailed) value of 0.027 <0.05, meaning that there are differences in pretest and post-test results after being given Rational Emotive Behavior Therapy behavior. This proves that Rational Emotive Behavior Therapy effectively reduces Self-Harm behavior in adolescents. Then, the Kruskall Wallis test results show an Asymp. Sig (2-tailed) of 0.227 > 0.05. there is no significant difference in reducing Self-Harm behavior in adolescents with the personality types of openness, Conscientiousness, Agreeableness, and Neuroticism